1974
DOI: 10.1073/pnas.71.12.4648
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Fibroblast Growth Factor, Insulin, Dexamethasone, and Serum on the Morphology of BALB/c 3T3 Cells

Abstract: The effects of serum, fibroblast growth factor, dexamethasone, and insulin on the morphology of two lines of BALB/c 3T3 cells are described and illustrated. Fibroblast growth factor, a polypeptide purified from bovine brain and pituitary glands, stimulates DNA synthesis and cell division in both sparse and confluent cultures of quiescent 3T3 cells. Cell Culture. Two lines of BALB/c 3T3 cells maintained in this laboratory were used. They have been described elsewhere (2). Cells were cultured at 370 in a CO2 inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0
2

Year Published

1974
1974
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 10 publications
(7 reference statements)
2
13
0
2
Order By: Relevance
“…In contrast, the parental A31 cells showed contact inhibition, with a regular cobblestone pattern in the monolayer culture. A morphological change similar to that of the transformed cells was observed when A31 cells were cultured in the presence of bFGF, as reported by Gospodarowicz and Moran (15).…”
Section: Resultssupporting
confidence: 63%
“…In contrast, the parental A31 cells showed contact inhibition, with a regular cobblestone pattern in the monolayer culture. A morphological change similar to that of the transformed cells was observed when A31 cells were cultured in the presence of bFGF, as reported by Gospodarowicz and Moran (15).…”
Section: Resultssupporting
confidence: 63%
“…In a given cell type, the actions of dexamethasone can vary between growth factors. In 3T3 cells, dexamethasone inhibits the growth promoting action of EGF but potentiates that of fibroblast growth factor (18,19). This suggests that the action of dexamethasone does not target a single cytoplasmic or nuclear mechanism distal to the interaction between growth factors and their cell surface receptors.…”
Section: Discussionmentioning
confidence: 92%
“…Dexamethasone is necessary to condition the cells in order that they might divide to reach a final density comparable to that seen with serum. When dexamethasone is present, insulin has little effect on cell growth; however, its effect on morphology is marked (10). We conclude that dexamethasone either prevents the degeneration that takes place in cells maintained in medium containing little serum, or it permits the cells to complete a division cycle initiated by FGF.…”
mentioning
confidence: 79%
“…Final cell densities observed after the addition of 10% serum were: 3.2 X 106 for cultures grown in FGF plus dexamethazone plus insulin, 2.2 X 106 for cultures grown in FGF plus dexamethasone, and 1.4 X 106 for cultures grown in 10% serum. Morphological studies (10) indicated that the addition of 10% serum to cells grown to confluency in the presence of 10% serum did not result in overcoming "contact inhibition." However, when 10% serum was added to cells grown in the presence of FGF plus dexamethasone or of FGF plus dexamethasone plus insulin, "contact inhibition" was not observed; the cells grew in double or triple layers and had a morphology similar to that of transformed cells (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation